Pengaruh Jenis Masalah pada Problem Based Learning terhadap Dinamika Metakognisi Siswa SMA Kelas X pada Konsep Stoikiometri - Issaura Sherly Pamela; Muhammad Rusdi; Asrial Asrial (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2013)
Innovation is needed in learning to make meaningful learning, so the student constructs their ownknowledge from the learning experience of learning process. One of the innovations is to integrate Problem Based Learning model. Problem Based Learning involves students to be active in every problem. Eleven problems type in Problem Based Learning that have different solving steps, due to every student different metacognition character potential and can change by given treatment. This research is a pre-experimental design: the pretest-posttest control and experimental group design with embedded experimental design. The metacognition character data were analyzed qualitaively, whereas the average grade data were analyzed quantitatively. The analysis of metacognition character shows the different metacognition characters and on learning process there is improvement of student achievement from 14% to 84.4%.